Natural intercultural mediation: reflections from a local experience - Jabbaz, Marcela; Moncusí Ferré, Albert (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2014)
This text provides a reflection on the intercultural natural mediation, its differentiation with respect to the professional mediation and its limitations within social exclusion politics. The authors base their arguments in information collected from a research performed in Valencia, with European funding and under the responsibility of three NGO that collaborated very actively in the fieldwork. The reflections are centered in the case of the Valencian neighborhood of Orriols. A first section describes the neighborhood. Later, different speeches of foreign and indigenous neighbors are undertaken and the relations among both are characterized. Finally, the authors define the natural intercultural mediation, with special attention to its fortresses and weaknesses. The authors emphasize that the potentialities of the mediation can be developed with a correct articulation between Administration and Civil Society and in combination with social politics of prevention and eradication of social exclusion
Keywords: Intercultural mediation; Natural Mediation; Conviviality; Interethnic relations